Is the Overturn of Gender Stereotypes the Key to Fertility Increase in Serbia? - Šobot, Ankica S. (Sociološki pregled, 2019)
The main question of this text is whether the change of traditional division of gender roles is really a factor that would make birth rate in Serbia closer to the level needed for population replenishment. A connection between gender models and fertility rate in European countries, which are characterized with different gender regimes, is discussed according to relevant demographic literature and statistical data. Likewise, the findings of conducted research studies in Serbia are the basis for consideration of gender models within family and gender aspects of parenthood as factors of childbearing decision. The specificities of economic development and widespread cultural norms determine the relation and influence of gender roles on fertility. The answer to the question that directed this text is discernable within this framework.
Keywords: low fertility; gender roles; social development; Europe; Serbia